Analysis of the feasibility of adding a grid-connected hybrid photovoltaic system to reduce electrical load - Moranain Mungkin; Habib Satria; Dina Maizana; Muzamir Isa; Syafii Syafii; Muhammad Yonggi Puriza (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The power generation system with hybrid system grid connected (HSGC) technology is an energy-saving technology that is able to compensate for electricity loads in an energy-efficient manner in today's technological advances. Electrical transient analyzer power (ETAP) simulation software is implemented so that the modeling will have an impact on the development of hybrid systems. Testing the reliability of the system is simulated at the load of school buildings, laboratories, mosques, and kindergarten schools. parameters obtained by evaluating the ratio of the voltage drop before and after the addition of photovoltaic. The value of the voltage drops decreases with the integration of hybrid photovoltaic. The school building panels experienced a voltage drop of 0.15%, reduced after the addition of photovoltaics and wind turbines. Then on the Laboratory panel, a voltage drops of 0.05% was obtained, on the mosque panel the voltage drop reached 0.11%, and on the kindergarten building panel the voltage drop reached 0.09% after the addition of photovoltaic hybrid. From this comparison it can be said that PV and wind turbines can affect the voltage drop and reduce the consumption of electricity loads from the grid caused by adding power from the hybrid photovoltaic hybrid to each load.